Reimagining business education : insights and actions from the business education jam - Carlile, Paul R.; Davidson, Steven H.; Freeman, Kenneth W.; Thomas, Howard, 1943-; Venkatraman, N. (Emerald Group Publishing Limited, 2016)
This book discusses the rationale for, and design of, the first Business Education Jam. It reviews key challenges and articulates a vision for how the role and delivery of business education could be reimagined in a time when business schools struggle to identify the innovations necessary to meet the needs of a changing world.